Preparation of the Log type of rock - log integration and Sequential Stratigraphy methodology in the complex reservoirs of the units, Tarma-Copacabana system in Madre de Dios Basin - Castillo Guzmán, Edson J. (2019)
Carbonaceous rocks in Peru have been little studied because of the mineralogical variability, their poorly understood sedimentation processes and the complexity of their rock attributes (porosity, permeability). The objective of the present research is to obtain an integrated log type that serves as a standard for the elaboration of geological sections and maps, in order to establish a predictive model, in an areal distribution of potential reservoirs within calcareous units. Tarma and Copacabana groups mainly composed of carbonaceous facies, with a lower proportion of silicoclastics and evaporites, all have thicknesses ranging from 800 to 1000 meters. Within the depositional model, 4 sequences have been identified in the third order, from Continental Environments to Distal marine. It is seen that within each sequence of third order have been related up to three sedimentary courts; (Continental), transgressive and high seas (platform), which integrates them with the attributes of rock, it is identified that the levels of porosity are found in the LST and HST systems.